ARE COMMERCIAL CUFFLESS BLOOD PRESSURE DEVICES BEING VALIDATED?. (June 2022) - Cox, James; Louka, Kyrollos; Avolio, Alberto P.; Tan, Isabella; Butlin, Mark
Abstract : Objective: Hypertension is an increasingly prevalent global disease with an overwhelming burden on society and the healthcare system. Undiagnosed hypertension and poor adherence to monitoring have been highlighted in the literature to be a key factor in addressing this issue. Wearable devices are a potential solution to this problem through offering continuous and convenient blood pressure (BP) measurements, unlike current cuff-based approaches. However, the validity of such novel devices is a limiting factor to their integration as a medical tool. This literature review aims to highlight the lack of validity of current commercial cuffless BP devices and the resulting impact on BP measurement and monitoring. Design and method: Investigators generated a list of commercial cuffless BP devices and search terms based on a preliminary search performed in Google and literature databases. Google Scholar, PubMed and Scopus were then systematically searched. Articles were included following a criterion on the basis that they must mention a cuffless BP device and have performed a comparison of measurements with a reference device, either cuff-based or invasive. Statistical analyses were then undertaken. Results: Two hundred and five search terms were generated. Following the systematic search there were 932 articles captured. After the inclusion and exclusion criteria was applied more than 90% of papers were excluded on the basis that they did not perform a validation, were in another language and/or were not relevant to blood pressure measurement. Of the 205 commercial devices initially searched only 11 of these had performed some sort of validity test. None of the devices had undertaken a validity test in accordance with the 2014 IEEE Standard for Wearable, Cuffless BP Measuring Devices or the 2019 amendment. Conclusions: Current cuffless BP devices lack published validity and as a result clinical utility. Performing stringent testing on the accuracy and reliability of devices will result in the progression and acceptance of such devices with the capacity to revolutionise BP measurement and therefore hypertension.